(untitled) (Applied Biological Research, 2024)
The functional groups have a vital role in insect physiology, behaviour, and adaptation to the environment and are crucial in biomimetics to replicate and adapt biological functions for diverse use ranging from medicine to material science and energy technologies. A study was conducted on Leptosia nina forewing scales to assess its chemical composition spectra using Fourier Transform Infrared Spectroscopic (FTIR) analysis. The identified functional groups from dorsal white, dorsal black spot, ventral white and ventral black spot areas of L. nina forewing composed of alcohols, phenols, aldehydes, aliphatic amine, alkanes, alkenes, alkyl halides, alkynes, aromatic groups,carboxylic acid groups, nitro compounds, amines, ester and ether with various stretches. The spectra showed minor variations in peaks in the four regions studied. The study is the first record revealing the functional groups of L. nina forewing scales.